IMPLEMENTASI MATA PELAJARAN AKIDAH AKHLAK & AL QUR’AN HADIS DALAM MEMBANGUN NILAI-NILAI RELIGIUS PADA PESERTA DIDIK - Akhmad MS (UNISAN JURNAL, 2024)
This research aims to describe and analyze the application of religious character development in fostering good morals at Mts Hidayatullah Martapura. The type of research used is descriptive qualitative field research. This research uses data collection techniques in the form of interviews, observation and documentation. The results of the research show that: The implementation of religious character education to foster good morals at MTS Hidayatullah Martapura is carried out through learning activities, school cultural activities and extracurricular activities, and this has gone well. The implementation of religious character education to foster good morals at MTS Hidayatullah Martapura has supporting and inhibiting factors in its implementation, both internal and external. Supporting and inhibiting factors in implementing it, namely. Supporting factors include: (a) a conducive situation, (b) programmed activities, (c) supporting infrastructure, (d) good and exemplary teacher leadership. Inhibiting factors include: (a) lack of communication between the school and parents, (b) lack of awareness among students, and (c) differences in school community understanding regarding religious character education. Efforts to implement religious character education to foster good morals at MTS Hidayatullah Martapura are carried out as closely as possible through real implementation of planning for the development of religious character education which is integrated into learning activities, school cultural activities and extracurricular activities accompanied by morals. and spiritual support from the environment. schools and evaluation of development planning programs.